Faktor-Faktor Sukses Wirausaha Wanita di Sumatera Barat - Indah Maya Sari (Fakultas Ekonomi Universitas Andalas, 2020)
Overpopulation in an area will affect labor market conditions, which is characterized by an increase in the number of unemployed in highly populated areas. Entrepreneurship is one solution that can help the economic condition. The entrepreneur can solve excess labor or help reduce unemployment. The high number of women in West Sumatra each year is a huge potential, especially in entrepreneurship. Success in entrepreneurship is the goal of every woman in entrepreneurship. This research aims to see how the factors of marital status, experience, and use of Information and Communication Technology (ICT) such as the use of the telephone and the internet influence women's success in entrepreneurship. This study uses primary data “raw data” Susenas 2019. The results show that marital status, telephone use and internet use and experience influence women's success in entrepreneurship in West Sumatra.